Cloud cuckoo land - Doerr, Anthony (London, Scribner, 2021)
Bound together by a single ancient text, the unforgettable characters of Cloud Cuckoo Land are dreamers and outsiders figuring out the world around them: thirteen-year-old Anna and Omeir, an orphaned seamstress and a cursed boy, on opposite sides of the formidable city walls during the 1453 siege of Constantinople; teenage idealist Seymour and octogenarian Zeno in an attack on a public library in present-day Idaho; and Konstance, decades from now, who turns to the oldest stories to guide her community in peril
Keywords: English Fiction